Fresh frozen bone in oral and maxillofacial surgery - Luigi Fabrizio Rodella; Marco Angelo Cocchi; Rita Rezzani; Pasquale Procacci; Lena Hirtler; Pierfrancesco Nocini; Massimo Albanese (Elsevier, 2015)
The aim of the current study was to review the use of fresh frozen bone (FFB) in oral and maxillofacial surgery. We performed a review of the articles published in the literature between 1976 and May 2014 analyzing three medical databases (PubMed, Cochrane Library, and Embase) and using specific search terms. Literature analysis on FFB applications in oral and maxillofacial surgery revealed 47 articles between 1976 and May 2014. There are 46 clinical articles and one review. Clinical articles are represented by 22 case reports and case series and 24 retrospective studies. Classifying the scientific production by year of publication, it is evident that especially during the last 6 years there was an increase of FFB graft use in oral and maxillofacial approaches. The literature analysis on FFB's use shows that its application in oral and maxillofacial surgery began slowly in 1992 with Perrott and since 2006 it had a real development. The recent significant increase emphasizes the importance of FFB for bone regeneration in oral and maxillofacial surgery. This review found consistent evidence of FFB's use increase in oral and maxillofacial surgery suggesting a valid instrument for bone regeneration. To date, risks connected to the infections' transmission and to the immunogenic potential are extremely low and could be considered practically absent. So, this is an important alternative in the preimplant reconstructive surgery.